The Gap between Students Expectations and Educational Services Provided for them Zanjan University of Medical Sciences 2007 - Fariba Arbouni; Alireza Shoghli; Saheb Badriposhteh; Mansour Mohajery (Kerman University of Medical Sciences, 2008)
Background & Objective : One of the main problems which must be considered by the universities of medical sciences nationwide is to establish a solidarity system for providing desirable services and use of strategic methods in order to increase quality of services Determining gap in quality of services can facilitate backgrounds for preparing programs for improvement of educational quality of services This study was performed to determine the gap between college students expectations and provided educational services in Zanjan University of Medical Sciences 2007 Methods : In this descriptive study 362 students in medical sciences participated Data was collected using a questionnaire based on SERVQUAL By filling in the questionnaires students defined realities and their expectations in five aspects of quality of services including physical trust reliability responsiveness and sympathy The gap in services was calculated by subtracting students scores in realities from their expectations Results: Results showed that there were gaps in all five aspects of quality of services The highest gap mean was in sympathy aspect (167) and then in aspects of responsiveness (162) reliability (154) and physical aspect (152) The least gap mean was in trust aspect (146) There was a significant difference between realities and expectations in all aspects (P=00001) Students of higher levels mentioned higher gaps in a significant way (P